Network interventions : engaging social networks to accelerate diffusion, improve performance, and speed organizational change - Valente, Thomas W. (Productivity Press, 2026)
Social networks are important sources of influence on many personal, organizational, community, and societal behaviors. Network interventions (NIs) are purposeful and planned efforts to use social networks or social network data to generate social influence, accelerate behavior change, improve performance or quality, and/or achieve desirable outcomes among individuals, communities, organizations, or populations.This book is designed to be a guide or primer on how to use the powerful and formal set of mathematical and computational tools developed in the network analysis field to engage individuals, communities, organizations, and/or populations to bring about change. This change can be the spread of information, culture changes, attitude shifts, or accelerating adoption of new behaviors. It is designed to inform medical and public health professionals who are often tasked with promoting behaviors that improve health or prevent disease at the individual, organizational, community, regional, and/or national levels. It is also designed to be a book useful when the chief medical officer of a hospital or medical care organization turns to a colleague and says, "[O]ur rate of handwashing (or insert X) is too low and we need to increase that." The colleague can then offer a copy of this book, which provides a wide-ranging set of options on how to achieve such changes. It can also be applied to non-healthcare organizations and settings whenever someone wants to bring about cultural or behavioral change. Some of these options, such as network-identified opinion leaders, have considerable evidence, while others have none. The robust evidence base for NIs provides the basis for this book, with the goal of providing practical guidance to enable more widespread use of them.The book focuses on how to actively harness the influence of networks to engage people and organizations in behavior change efforts and improve the development and delivery of interventions.Thomas W. Valente, PhD is Professor in the Department of Population and Public Health Sciences, Keck School of Medicine, University of Southern California, Los Angeles, CA, USA.
Keywords: Diffusion of innovations -- Social aspects.; Network analysis (Planning); Organizational behavior -- Social aspects.; Organizational change -- Social aspects.; elektronické knihy; electronic books